Developing Speaking Skill Using Retelling Story: Penelitian - Wahyuda Kusumah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
One of the essential skills in English is Speaking Skill. Speaking must be mastered in learning, but there were some challenges for the students of  Villa Mas Senior high School, Jakarta to make them comfort, easy to pronounce, to say some sentences, to keep in touch  in English, They did not have selves confident to utterance in English, to answer this opportunity in practicing English using retelling story technique. The aim of this research is to know the condition of students in presenting something in English and also the benefits of using that. This research was a qualitative method. The researcher gave motivation for students to brave to speak English and also to remind the students not to shy to speak English and then don’t be afraid to make mistakes, develop some aspects of speaking such as pronunciation  in speaking English, the mindset, mentality,  were built from students in acting this lesson. Based on the result of the research, the students have strong mentality in speaking English in front of class.